Comparative Study of the Volume Charge Density in Most General Lorentz Transformation and Quaternion Lorentz Transformation - Baizid, A. R. (Journal of Scientific Research, 2019)
Lorentz transformation is the relation of space and time coordinates of one inertial frame relative to another inertial frame in special relativity. In this paper we have studied the volume charge density in most general and quaternion Lorentz transformations for different angles with different velocities of the moving frame. We have also used numerical data to see the comparative situation.